Um Modelo Analítico para Estimar o Consumo de Energia de Aplicações Web no Nível de Transaçõ es - Ferreira, Alex R.; Vidal, Denner S. L.; Reis, Valéria Q. dos; Correa, Sand Luz (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2017: Anais do XXXV Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2017)
Modern enterprise servers provide several features to manage the power consumption of their subsystems. In environments with high computational demand, these features can significantly reduce energy consumption. However, in order to make proper use of such resources, we need to understand how the applications that run in these servers consume the computational resources and the implications of such usage for the overall power and energy consumption. In this work, we propose an energy model to characterize the energy consumption of enterprise servers that host Web systems. Unlike other works in the literature, our model captures the consumption pattern of these applications at the level of transactions and for each tier of the system. In addition, our model depends solely on the CPU utilization and on server architectural parameters, which can be easily obtained in current production environments. We demonstrate the effectiveness of our model in a real experimental environment, based on the TPC-W benchmark. Results show that our model is able to estimate the energy consumption of Web applications with errors in the same order of magnitude as those presented by previous work.